Distribution of clams Meretrix casta (Chemnitz) in the Sadras backwaters - Ramgopal, S; Nair, K V K; Azariah, Jayapaul (Indian Journal of Fisheries, 2011)
Resource potential of clams was studied from February 1988 to January 1989 in the Sadras backwatersat Kalpakkam. The distribution of clams in the backwaters was not uniform. The biomass of clams variedfrom 56 to 6416 g/m". Population density varied from 11 to 2066 clams/m*. Population mostly comprisedMeretrix casta (81.7 to 96.8%). The spatfall of clams was recorded in May and it continued up to July. Thedata established that sediment characteristics, rather than hydrographic parameters, greatly influence thedistribution of clams in the backwaters